Functional Characterization of Cotton C-Repeat Binding Factor Genes Reveal Their Potential Role in Cold Stress Tolerance - Liu, Jiangna; Magwanga, Richard Odongo; Xu, Yanchao; Wei, Tingting; Kirungu, Joy Nyangasi; Zheng, Jie; Hou, Yuqing; Wang, Yuhong; Agong, Stephen Gaya; Okuto, Erick; Wang, Kunbo; Zhou, Zhongli; et al. (Frontiers in Plant Science, 2021)
Low temperature is a common biological abiotic stress in major cotton-growing areas. Cold stress significantly affects the growth, yield, and yield quality of cotton. Therefore, it is important to develop more robust and cold stress-resilient cotton germplasms. In response to climate change and erratic weather conditions, plants have evolved various survival mechanisms, one of which involves the induction of various stress responsive transcript factors, of which the C-repeat-binding factors (CBFs) have a positive effect in enhancing plants response to cold stress. In this study, genomewide identification and functional characterization of the cotton CBFs were carried out. A total of 29, 28, 25, 21, 30, 26, and 15 proteins encoded by the CBF genes were identified in seven Gossypium species. A phylogenetic evaluation revealed seven clades, with Clades 1 and 6 being the largest. Moreover, the majority of the proteins encoded by the genes were predicted to be located within the nucleus, while some were distributed in other parts of the cell. Based on the transcriptome and RT-qPCR analysis, Gthu17439 (GthCBF4) was highly upregulated and was further validated through forward genetics. The Gthu17439 (GthCBF4) overexpressed plants exhibited significantly higher tolerance to cold stress, as evidenced by the higher germination rate, increased root growth, and high-induction levels of stress-responsive genes. Furthermore, the overexpressed plants under cold stress had significantly reduced oxidative damage due to a reduction in hydrogen peroxide (H2O2) production. Moreover, the overexpressed plants under cold stress had minimal cell damage compared to the wild types, as evidenced by the Trypan and 3,3′-Diaminobenzidine (DAB) staining effect. The results showed that the Gthu17439 (GthCBF4) could be playing a significant role in enhancing cold stress tolerance in cotton and can be further exploited in developing cotton germplasm with improved cold-stress tolerance.